"It's a Big Umbrella": Uncertainty, Pentecostalism, and the Integration of Zimbabwe Exemption Permit Immigrants in Johannesburg, South Africa. Issue 1 (1st June 2021) - Chimbidzikai, Tinashe
Abstract: This article questions the dominant narrative that considers displaced persons as victims, powerless, and lacking agency to shape their individual and collective conditions. Based on an ethnographic study of largely Zimbabwe Exemption Permit holders living in Johannesburg, the article argues that Pentecostalism offers an alternate worldview that draws on religious beliefs and practices to express triumph over everyday adversities and vicissitudes of forced mobility. The article concludes that such beliefs and practices embolden and espouse individual and collective agency among "born-again" migrants, as they mobilize religious social networks for individuals to make sense of the uncertainties engendered by displacement.